Salmonella Effectors SseF and SseG Interact with Mammalian Protein ACBD3 (GCP60) To Anchor Salmonella-Containing Vacuoles at the Golgi Network - Yu,XJ; Liu,M; Holden,D (mBio, 2016)
Following infection of mammalian cells, Salmonella enterica serovar Typhimurium (S. Typhimurium) replicates within membrane-bound compartments known as Salmonella-containing vacuoles (SCVs). The Salmonella pathogenicity island 2 type III secretion system (SPI-2 T3SS) translocates approximately 30 different effectors across the vacuolar membrane. SseF and SseG are two such effectors that are required for SCVs to localize close to the Golgi network in infected epithelial cells. In a yeast two-hybrid assay, SseG and an N-terminal variant of SseF interacted directly with mammalian ACBD3, a multifunctional cytosolic Golgi network-associated protein. Knockdown of ACBD3 by small interfering RNA (siRNA) reduced epithelial cell Golgi network association of wild-type bacteria, phenocopying the effect of null mutations of sseG or sseF. Binding of SseF to ACBD3 in infected cells required the presence of SseG. A single-amino-acid mutant of SseG and a double-amino-acid mutant of SseF were obtained that did not interact with ACBD3 in Saccharomyces cerevisiae. When either of these was produced together with the corresponding wild-type effector by Salmonella in infected cells, they enabled SCV-Golgi network association and interacted with ACBD3. However, these properties were lost and bacteria displayed an intracellular replication defect when cells were infected with Salmonella carrying both mutant genes. Knockdown of ACBD3 resulted in a replication defect of wild-type bacteria but did not further attenuate the growth defect of a ΔsseFG mutant strain. We propose a model in which interaction between SseF and SseG enables both proteins to bind ACBD3, thereby anchoring SCVs at the Golgi network and facilitating bacterial replication.